Linguistic Landscape in the West Bank: Road Signs as Manifestations of Occupation - Ujvari, Montaser Motia (International Journal of Language and Literary Studies, 2022)
This study investigates road signs put in place by Israel in Area C in the occupied West Bank. It discusses how language on road signs in the West Bank serve as tool that enforces Israeli dominance over the area and blurs the Palestinian existence. This dominance is reflected in the excessive placement of signs referring to Israeli settlements compared to signs referring to Palestinian communities, transliteration of Arabic names of sites into Hebrew, and deletion of Arabic, a language associated with the Palestinian identity, from road signs. In addition, this paper demonstrates how the exclusion of Arabic from road signs, especially brown signs referring to tourist attractions, serves as a barrier that aims at limiting Palestinians’ access to some parts of the West Bank and shows Israeli discriminatory practices against Palestinians. Moreover, this paper explains how warning signs at Israeli checkpoint construct the concept of the “Palestinian islands” by dividing the West Bank into disconnected enclaves surrounded by an ocean of Area C making the idea of establishing an independent Palestinian state seem impossible. Finally, this study records instances of Palestinians’ resistance to Israel through vandalism of signs that were placed by the Israeli authorities in Area C.